Atopic Dermatitis and the Risk of Infection in End-Stage Renal Disease - Rushan I. Momin; Stephanie L. Baer; Jennifer L. Waller; Lufei Young; Sarah Tran; Varsha Taskar; Wendy B. Bollag (Medicina, 2023)
Background and Objectives: Atopic dermatitis (AD), also known as eczema, is a common chronic inflammatory skin condition affecting 16.5 million adults in the United States. AD is characterized by an impaired epidermal barrier that can predispose individuals to infection. End-stage renal disease (ESRD) is also commonly complicated by infections due to chronic vascular access and immune-system dysfunction, possibly related to uremia. Multiple studies have reported that renal disease is a common comorbidity in adults with atopic dermatitis. The aim of this study was to determine whether AD is a risk factor for certain infections in patients with ESRD. Materials and Methods: Using the United States Renal Data System, a retrospective cohort analysis was conducted on adult ESRD patients initiating dialysis between 2004 and 2019 to investigate associations between infections and AD in this population. Results: Of 1,526,266 patients, 2290 were identified with AD (0.2%). Infectious outcomes of interest were bacteremia, septicemia, cellulitis, herpes zoster, and conjunctivitis. In all infectious outcomes except for conjunctivitis, patients with the infectious outcomes were more likely to carry a diagnosis of AD. After controlling for demographic and clinical covariates, AD was associated with an increased risk of cellulitis (adjusted relative risk (aRR) = 1.39, 95% confidence interval (CI) = 1.31–1.47) and herpes zoster (aRR = 1.67, CI = 1.44–1.94), but not with bacteremia (aRR = 0.96, CI = 0.89–1.05), septicemia (aRR = 1.02, CI = 0.98–1.08), or conjunctivitis (aRR = 0.97, CI = 0.740–1.34). Conclusions: Overall, after controlling for demographic and clinical covariates and adjusting for person-years-at-risk, AD was associated with an increased risk for some, but not all, infections within the population of patients with ESRD.